O ESTÁGIO SUPERVISIONADO OBRIGATÓRIO NA FORMAÇÃO DOCENTE: UM ESTUDO A PARTIR DE UM CURSO DE PEDAGOGIA NA MODALIDADE A DISTÂNCIA - LUSSICH, CLEONICE DE ALMEIDA CUNHA (2017)
The purpose of this thesis was to make explicit the formative value and meaning of the compulsory supervised internship for graduates of a Distance Education course in order to construct the knowledge necessary for the practice, as well as the process of constitution of the professional identity of the pedagogue. The qualitative research carried out a study about the proposal and development of the compulsory supervised internship of a Distance Education course of a Community Higher Education Institution located in São Paulo and the collaborating subjects were graduates, graduates, coordinator and teachers/tutors of said course. The instruments for data collection were: application of a questionnaire to delineate the profile of the graduates, conduct interviews with the graduates and elaborate reports of experience by the coordinator and teachers. We also carried out an analysis of the literature and documentary review of the history of distance education in the educational context of the National Curricular Guidelines for Pedagogy, as well as the principles and fundamentals of the supervised internship of the course investigated. The theoretical contributions were anchored, mainly, in authors as: Bahia (2012, 2013, 2015); Pimenta (2009); Pimenta and Lima (2010); Gatti (2009; 2010), Gatti, Barreto and André (2011); Libano (2003, 2004, 2006); Lima (2012); Moran (2009; 2011; 2013); Piconez (2005); Scheibe (2006; 2007); Silva (2003); Tardif (2000, 2003) and Zabalza (2014). The research data evidenced that the experience of the internship in the distance pedagogy course of the investigated institution is configured as a space/time of construction of teacher knowledge and professional identity, considering some differentials of the modality, observed and analyzed, and that indicate the concern with the formative quality. It was also possible to infer that institutions that work with teacher training in the distance modality cannot be generically classified as certifiers and offer a light training, since it is necessary to carefully analyze the proposition, the assumptions, the procedures of the pedagogical projects, the development of the classes, the activities proposed, the monitoring and evaluation of the graduates, the virtual environment and the available materials, among other very specific issues of this type of education. In general, the results indicate that the course under study presents conditions for adequate training and is adjusted to the official guidelines and that, despite the observation of some gaps and limitations, there is scope for overcoming these.